Malignant transformation of a residual cerebellopontine angle epidermoid cyst. (November 2016) - Pikis, Stylianos; Margolin, Emil
Highlights: Malignant transformation of a remnant benign intracranial epidermoid cyst (EC) occurs rarely. Time to malignant transformation of a remnant intracranial EC is variable, thus long-term clinical follow-up is necessary. Prognosis of malignant transformation is poor and optimal management is unclear. Abstract: Malignant transformation is a rare but devastating complication following partial resection of an intracranial epidermoid cyst (EC). Time to malignant transformation is highly variable and optimal management is unclear. A literature search from 1965 to January 2016 identified manuscripts discussing clinical presentation, management, and outcome of malignant transformation of a remnant intracranial EC. One male patient diagnosed with malignant transformation of a remnant intracranial EC in our institution was also included in the study. There were 21 patients with malignant transformation of a remnant intracranial EC, including the current patient. Mean age was 51.4 years (range 36 to 77) and there was a female predominance (12 women, 9 men, ratio 1.33:1). The mean time interval from partial resection of a benign intracranial EC to malignant transformation was 7.74 years (range from 3 months to 33 years). Surgical resection of the tumor alone was the treatment of choice in 10 patients with one of them requiring a second operation and radiotherapy 2 months following the first operation. Adjuvant treatment modalities were employed in 11 patients and included radiotherapy (n = 4), stereotactic radiosurgery (SRS) (n = 3), chemotherapy (n = 1), chemotherapy combined with SRS (n = 1) and with radiotherapy (n = 1) and radiotherapy combined with SRS and followed by a second tumor resection (n = 1). Follow-up period ranged from 1 day to 5 years and 11/19 patients (57.8%) were reported dead on follow-up. Prospective studies are required to define the optimal management of malignant transformation of remnant intracranial EC.